Studi Kritis terhadap Buku Siswa Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti - Achmad Maimun (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2020)
The improvement of learning quality has been made through various efforts. The publication of textbooks is one of the efforts used to support the 2013 Curriculum implementation. The textbooks improvement efforts have been continually made by publishing the revised edition. However, the publication of the revised edition does not guarantee that the revision is better than the previously published edition. Some reviews found that the revised version contains several mistakes while it has not occurred to the previous edition. This finding is interesting to be critically scrutinized within a more in-depth analysis. Thus, the problems of the edition of the revised textbook underlie this research study. Based on the research objectives, this study is a library research or literature review. The primary resources of this study are the PAI and Budi Pekerti textbooks for grade 7th up to 9th. The analysis method used in this study is a content analysis that critically examines the substance of textbooks' content. In detail, this study also used the comparative method of analysis. This study found that still there are several shortcomings in the PAI and Budi Pekerti textbooks for all levels. In terms of making the research findings more understandable and readable, the elicited problems found in the textbooks are classified based on aspects of language and writing, conceptual, relevance and coherence, material repetition, and psychological sensitivity. These findings can be used by policymakers in developing the textbooks, for the process of improvement and refinement in the future.